How Much and Why? Conservation Behavior and Valuation in Katunggan Coastal Ecopark, Mindanao Island, Philippines (Forest and Society, 2025)
Mangrove forests are among the most productive and valuable ecosystems, providing critical services such as shoreline protection, fisheries support, and carbon sequestration. Despite their ecological and economic significance, mangrove forests continue to decline at an alarming rate due to land conversion for aquaculture, urban expansion, overharvesting, and climate-related impacts. Although national and community-based conservation programs exist in the Philippines, many of these efforts have struggled due to limited public participation and a lack of insight into how local communities perceive and value mangrove ecosystems. This study surveyed 503 residents living near the Katunggan Coastal Ecopark in Mindanao Island, Philippines, to examine how conservation attitudes, perceived threats, knowledge, utilization, and sociodemographic factors shape conservation action and willingness-to-pay (WTP) for mangrove protection. Respondents generally exhibited high knowledge of mangroves, with strong recognition of climate and human-induced threats, as well as high conservation attitudes and actions, and a low reliance on mangroves for their livelihood. Most expressed support for conservation through monetary contributions (82.4%), although some cited financial constraints, skepticism toward fund use, or preference for non-monetary participation. Structural equation modeling (SEM) revealed that perceived threat and conservation attitude significantly influenced conservation actions, while knowledge, conservation actions, monthly income, and sex at birth predicted WTP. The log-normal interval regression model estimated a mean annual WTP of USD 12.29 (₱703.53) and a median of USD 1.59 (₱91.01), indicating a right-skewed distribution. These findings offer critical insight into the cognitive and behavioral drivers of mangrove conservation support. They can inform inclusive, flexible payment mechanisms that ensure greater community participation in sustainable mangrove ecosystem management.
Keywords: Community-based conservation; Environmental valuation; Mangrove conservation; Structural Equation Modelling (SEM); Mindanao; Philippines